Reconceptualizing literacy in the new age of multiculturalism and pluralism - Schmidt, Patricia Ruggiano, 1944-; Lazar, Althier M. (Language, literacy, and learning., 2016)
The 2nd Edition of Reconceptualizing Literacy in the New Age of Multiculturalism and Pluralism honors the genius of Dr. Peter Mosenthal. His contributions to the field of literacy were unprecedented. Many described him as a superb researcher who never lost sight of the purpose of education. He made us laugh as he led us in a nursery rhyme song during his National Reading Conference (LRA) Presidential Address and made us think as he explained the significance of educational implications in all research articles. He also mentored and taught graduate students in gentle and carefully attentive ways, showing his respect and appreciation for the work of each individual in the field. He was a remarkable person.The second edition of this book includes many experienced and new scholars from around the world. Qualitative and quantitative research methodologies are scattered throughout and the practical and theoretical are well represented. New Literacies and Global Perspectives are added sections in this volume. In this era of the "Common Core", Reconceptualizing Literacy in the New Age of Multiculturalism and Pluralism, presents a rational educational balance for literacy development across the curriculum.